Synthesis and characterization of pH-sensitive glucomannan-poly(acrylic acid) hydrogels for 5-aminosalicylic acid controlled delivery systems - Lam Son Le; Thuy Trang Le; Thi Van Thi Tran; Vinh Phu Nguyen; Quang Man Nguyen; Trung Hieu Le (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên, 2022)
In this study, glucomannan-poly(acrylic acid) hydrogels were synthesized under different conditions. The hydrogels consist of glucomannan and acrylic acid and are crosslinked by N,N-methylene-bis-(acrylamide). The structure and morphology of the hydrogels were investigated by using Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscope (SEM). The swelling ratio, biodegradation and pH-sensitive properties, relationship between hydrogel swelling rate and 5-ASA adsorption-desorption capacity, influence of medium pH on 5-ASA desorption, and 5-ASA adsorption kinetics were studied. The swelling ratio of the synthesized hydrogel samples is 16.70–56.21 times. This ratio is low in the pH 1.0 media and increases significantly in the pH 7,4 media. The hydrogels are biodegradable in the presence of cellulase (400 U·mg–1) in a pH 7.4 phosphate buffer at 37 °C (69.8% after ten days; the cellulase concentration 1.5 g·L–1). The hydrogels exhibit high adsorption and desorption capacities for 5-ASA. The adsorption kinetics follows the pseudo-first-order model. These hydrogels can be applied to smart drug delivery systems.